Effect of tear fluid sampling and processing on total protein quantity and electrophoretic pattern - Kristina Krajcikova; Gabriela Glinska; Vladimira Tomeckova (Taiwan Journal of Ophthalmology, 2022)
Human tears contain more than 1500 proteins that could be diagnostically relevant. To date, numerous candidates on a biomarker of protein origin were identified for ocular and systemic diseases. However, the suitable sampling method is still the subject of discussion. To address the need for a description of sampling methods properties for possible clinical analyses, we studied a total protein concentration and electrophoretic pattern of tear fluid collected by capillary tubes, Schirmer strips, cellulose microsponges, and flushing. The total protein concentration was 4.339 μg/μL ± 1.905 μg/μL, 0.967 μg/μL ± 0.117 μg/μL, 0.022 μg/μL ± 0.016 μg/μL, and 0.008 μg/μL ± 0.006 μg/μ for the capillary tubes, Schirmer strips, flushing, and cellulose microsponges, respectively. Sodium dodecyl sulfate polyacrylamide electrophoresis showed the different patterns of tear proteins obtained by the above-mentioned sampling methods. These differences could originate from the use of a bigger amount of extraction reagent that was not used in the case of capillary tubes, and retention of the proteins by strips and sponges. Taken together, capillary tubes, Schirmer strips, cellulose microsponges, and flushing represent sensitive and convenient sampling methods for tear fluid collection. For the isolation of proteins from strips and sponges, and for the flushing, less than 100 μL of a reagent should be used to ensure the sufficient concentration of the biomarkers in a trace amount.